2014
DOI: 10.1007/s00586-014-3491-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cervical sagittal alignment and quality of life in ankylosing spondylitis

Abstract: Cervical sagittal parameters were found to be significantly different in AS patients and normal controls. Correlation analysis revealed significant relationships between radiographic parameters and QOL. In particular, C2-C7 SVA was found to be a significant predictor of QOL in AS patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 21 publications
2
28
0
Order By: Relevance
“…As PI-LL mismatch has been previously reported to influence post-operative residual symptoms, it is possible that abnormal T1S-CL could represent a similar degenerative process in the cervicothoracic junction and marker for overall deformity and imbalance [21]. T1S-CL mismatch has also been correlated with inferior patient-reported outcomes by Lee et al, an observation which is sustained in this report [9].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…As PI-LL mismatch has been previously reported to influence post-operative residual symptoms, it is possible that abnormal T1S-CL could represent a similar degenerative process in the cervicothoracic junction and marker for overall deformity and imbalance [21]. T1S-CL mismatch has also been correlated with inferior patient-reported outcomes by Lee et al, an observation which is sustained in this report [9].…”
Section: Discussionsupporting
confidence: 71%
“…Traditionally, abnormal cervical kyphosis or scoliosis were enough to characterize cervical deformity, but recent reports have suggested that CD on radiographic assessment may also be defined based on other parameters [8]. These include measures that have been found to significantly correlate with disability, including mismatch between T-1 Slope and cervical lordosis (T1S-CL) and C2-C7 sagittal vertical alignment (C2-C7 SVA), for example [8][9][10]. Recently, Passias et al used a three-part definition for CD that incorporated all three criteria in surgical ASD patients, resulting in a post-operative cervical deformity rate of 63 % [11].…”
Section: Introductionmentioning
confidence: 99%
“…These reciprocal changes may generate a more homeostatic and natural alignment. However, unintended overcorrection or unforeseen alterations outside of the surgical region may compromise sagittal alignment with a substantial negative impact on pain and quality-of-life scores [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with cervical myelopathy with OPLL in more than three segments, posterior decompression is more attractive than anterior decompression because this procedure can avoid the need for an anterior route or major strut graft-related problems, such as cerebrospinal fluid leakage, pseudoarthrosis, or graft dislodgment 26,31) . Posterior decompression surgeries were reported to diminish cervical lordosis preoperatively, and postoperative kyphotic deformities have been considered a source of pain and disability 15,21,22,29,32) . Therefore, it is important to evaluate the correlation between clinical outcomes and cervical sagittal alignment after posterior cervical decompression.…”
Section: Introductionmentioning
confidence: 99%